SURVEI TINGKAT KETERBATASAN AKSES TEKNOLOGI DAN MINAT BELAJAR SISWA PADA PEMBELAJARAN PPKN DI SEKOLAH DASAR - Fitriana, Desi; Chan, Faizal; Alirmansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the condition of limited access to technology and the level of students' interest in learning Civics Education (PPKn) in Elementary School. This research used a quantitative approach with a descriptive survey method. The research subjects were 49 fourth, fifth, and sixth grade students selected through purposive sampling. Data were collected using a Guttman scale questionnaire validated through expert judgment. The data were analyzed using descriptive statistics by calculating the mean and achievement percentage. The results showed that the level of limited technology access was in the "High" category with an achievement percentage of 76.33%. Meanwhile, the level of students' learning interest in PPKn was in the "Low" category with an achievement percentage of 76.94%. The conclusion indicates that significant limitations in technology access are in line with low student interest in PPKn learning. This study recommends the need to develop creative learning strategies that do not fully depend on technology and to improve digital infrastructure in elementary schools.